2017
DOI: 10.1080/14767058.2017.1330330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal age on spontaneous abortion during the first trimester in Northeast China

Abstract: These results revealed that the kinds of fetal abnormalities, numbers of abortions, and chromosomal abnormality rates increased with increasing maternal age. The most common trisomy types in spontaneous abortions were closely related to maternal age. We hypothesize whether the larger probability of chromosomal abnormalities is due to increased mutation rate with maternal age, or due to a worse in-utero conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Chromosome abnormalities usually result in developmental arrest and spontaneous abortion. Our laboratory historically [28] used FISH technology for testing chorionic villi, and found that the kinds of fetal abnormalities, numbers of abortions, and chromosomal abnormality rates increased with increasing maternal age, and we hypothesize whether the larger probability of chromosomal abnormalities is due to increased mutation rate with maternal age, or due to a worse in-utero conditions. FISH probes for abortion samples could detect more chromosomal numerical abnormalities for it can detect 16/22 addtionally.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome abnormalities usually result in developmental arrest and spontaneous abortion. Our laboratory historically [28] used FISH technology for testing chorionic villi, and found that the kinds of fetal abnormalities, numbers of abortions, and chromosomal abnormality rates increased with increasing maternal age, and we hypothesize whether the larger probability of chromosomal abnormalities is due to increased mutation rate with maternal age, or due to a worse in-utero conditions. FISH probes for abortion samples could detect more chromosomal numerical abnormalities for it can detect 16/22 addtionally.…”
Section: Discussionmentioning
confidence: 99%
“…As know, miscarriage is a common pregnancy outcome and more likely to happen among women aged 35 years and older. It is due to fetal abnormalities and chromosomal abnormality linked to mutation by rising maternal age, or worse in-utero conditions [21]. In our setting, this was manifest among Caucasian women.…”
Section: Discussionmentioning
confidence: 73%
“…Although female age and BMI are first line prognostic factors in human reproduction, we did not find significant differences between the age or BMI groups with miscarriage. Winter et al (2002) concluded that there was no significant relationship between age, obesity, and the miscarriage rate, while Dai et al . (2018) pointed out that women over the age of 40 had significantly higher early miscarriages rates (60.6%) than women under the age of 40.…”
Section: Discussionmentioning
confidence: 99%